Caracteriza??o de matrizes, toler?ncia ? desseca??o de duas leguminosas e variabilidade gen?tica de Anadenanthera spp. em florestas tropicais secas - Silva, Fabr?cio Francisco Santos (2019)
The selection of mother-plants is important for identifying, locating and delimiting areas for seed collection of forest species. The seed collect improve farmers? quality of life and help conservation environmental. Other step in conservation is identification of these plants could help in the selection of desiccation tolerant species in seasonally dry tropical forests (SDTF). Post-germinative desiccation tolerance (DT) is directly linked to the success of seedling survival of SDTF species. Cenostigma pyramidale is endemic to Caatinga, Anadenanthera colubrina and Anadenanthera peregrina which are widely distributed trees in SDTF. Tools used to study forest trees are important for the conservation of genetic resources. The objective of this study was to characterize mother-trees and to evaluate post-germinative DT of A. colubrina and C. pyramidale, as well as to evaluate the genetic variability of the Anadenanthera spp. This study presents a list of mother-trees of two legumes, as well as their detailed location. Sixty plants were registered in seven municipalities in Brazil: Uberl?ndia-MG and Planaltina-DF from Cerrado; Corumb?-MS from Pantanal; Canind? de S?o Francisco-SE, Lagoa Grande-PE, Petrolina-PE and Juazeiro-BA from Caatinga. For each marked plant, the following details were collected: dendrometric data, geographic coordinates and soil type. Anadenanthera colubrina and C. pyramidale seedlings of different sizes were separated into four Initial Root Length (IRL) categories and dried for 24 and 72 h. The seedling survival was evaluated at 7 and 14 days after rehydration (DAR). DNA was extracted from the leaves. A UPGMA dendrogram was generated using the Jaccard similarity index based on the genetic distance of 39 alleles and nine loci. An analysis of molecular variance was conducted using total decomposition among and within the populations of Anadenanthera spp. Gene flow (Nm) was estimated by the number of migrants, based on the parameter ?ST. The plant height of A. colubrina and C. pyramidale ranges from 4 to 42.5 m and 3 to 10 m, respectively. Ten types of soils were categorized. Anadenanthera colubrina and C. pyramidale were tolerant to post-germination desiccation. The survival rate of the A. colubrina seedlings with IRL between 7.00 and 10.99 mm that were dried for 24 h was 70% at 7 DAR. The survival rate of the C. pyramidale seedlings with IRL between 1.00 and 6.99 mm that were dried for 72 h was 96% at 7 DAR. At 14 DAR, C. pyramidale seedlings longer than 6.99 mm when dessicated were dead. The survival of seedlings of A. colubrina and C. pyramidale to desiccation, has a direct effect on the recruitment of SDTF species, specially during dry spells or drought years. The size of the alleles varied from 175 bp to 794 bp. The averages for allelic frequency, polymorphism information content (PIC) and heterozygosity were 0,58; 0,52 e 0,45, respectively, demonstrating the high capacity for detecting genetic variability. The coefficient of similarity varied between 20 and 80%, with a cophenetic value of 0,81. The two Bayesian clusters divide A. colubrina and A. peregrina. The genetic variability among the population is high, ?ST = 0,217 (P < 0,001), restricting the Nm to one migrant per generation (0,9). With the present study we conclude that (1) The mother-trees marked in the Caatinga ecosystem presented lower total height in relation to the Pantanal and Cerrado ecosystems trees.; (2) As a survival strategy, some seedlings of both species lose the primary root and emit adventitious roots after desiccation; (3) Population genetics can be studied using these markers, which also help in the taxonomic identification of Anadenanthera Speg. This work can be used as reference for future field studies of A. colubrina and C. pyramidale and in seed collection excursions of A. colubrina and C. pyramidale